Snowy Owls in central North America have regular migration and high philopatry to wintering sites though not always to home ranges - Karen L Wiebe; Mark T Bidwell; Rebecca A McCabe (Avian Conservation and Ecology, 2023)
Understanding the threats faced by a bird species requires a knowledge of their movements throughout the annual cycle and, for migratory species, the degree of connectivity between breeding and wintering sites. We studied the philopatry of Snowy Owls ( Bubo scandiacus ) tagged in central North America to their wintering sites on the Canadian prairies. The tracking of 16 owls over a period spanning six winters revealed consistent and predictable north-south migration trajectories, in contrast to populations farther to the west and east. Individuals were strongly philopatric to the central prairie region, but at a finer spatial scale, winter home ranges did not always overlap between successive years. Both sexes showed periods of nomadic searching for prey over a similar spatial scale, but males tended to settle closer to previous home ranges on average (88 km) than females (149 km). We hypothesize that the socially dominant females are better able to monopolize the spatially unpredictable hotspots of small mammal prey whereas males rely more on familiarity with a previous home range when settling. The population of Snowy Owls in central North America thus shows greater connectivity to wintering sites than do Snowy Owls documented elsewhere, probably related to the relatively high abundance and predictability of small mammal prey on the prairies. Maintaining prairie habitat on a large spatial scale that supports small rodents will be crucial to maintaining populations of Snowy Owls in the central part of the continent.